2020
DOI: 10.2147/prbm.s248540
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gender Differences in Problem Gamblers in an Online Gambling Setting</p>

Abstract: Background: Problem gambling traditionally is markedly more common in men than in women. However, recent data in online gamblers have indicated at least a comparable risk of problem gambling in women in this subgroup. The present study aimed to compare the characteristics of male and female moderate-risk and problem gamblers in online gamblers in Sweden. Methods: In a web survey addressing online gamblers (past-year online gambling on 10 or more occasions), women and men with moderate-risk or problem gambling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 56 publications
5
20
1
2
Order By: Relevance
“…However, within the sample of gamblers (all respondents who did not endorse being a non-gamblers both now and prior to the pandemic), women were significantly more likely to report an increase, and this association only marginally lost its statistical significance in the regression analysis. It has been shown previously that while men are typically over-represented among problem gamblers, female problem gamblers may display a higher degree of severity, and higher rates of psychiatric comorbidity, than male problem gamblers (Håkansson and Widinghoff, 2020a). In a Scandinavian setting, in recent years, it has been shown that in highly online-based gambling markets, women's risk of endorsing problem gambling criteria may be comparable to that of men, in some contrast to what has been seen traditionally (Håkansson and Widinghoff, 2020b).…”
Section: Discussionmentioning
confidence: 95%
“…However, within the sample of gamblers (all respondents who did not endorse being a non-gamblers both now and prior to the pandemic), women were significantly more likely to report an increase, and this association only marginally lost its statistical significance in the regression analysis. It has been shown previously that while men are typically over-represented among problem gamblers, female problem gamblers may display a higher degree of severity, and higher rates of psychiatric comorbidity, than male problem gamblers (Håkansson and Widinghoff, 2020a). In a Scandinavian setting, in recent years, it has been shown that in highly online-based gambling markets, women's risk of endorsing problem gambling criteria may be comparable to that of men, in some contrast to what has been seen traditionally (Håkansson and Widinghoff, 2020b).…”
Section: Discussionmentioning
confidence: 95%
“…Among treatment-seeking patients of a treatment facility in the present setting, in a previous study around half of men, but virtually no women, reported problematic sports betting [ 16 ]. In survey data from online moderate-risk gamblers, men were significantly more likely to report sports betting, whereas women were significantly more likely to report online casino gambling [ 17 ]. Thus, effects on self-exclusion from the nearly total lock-down of sports events would likely affect male self-exclusion behavior more than in women; however, this was not apparent here.…”
Section: Discussionmentioning
confidence: 99%
“…From mid-March to mid-May 2020, major sports events and opportunities for sports betting were cancelled [ 13 ]. Gambling habits differ strongly across gender; men are considerably more likely to report sports betting and women are more likely to report betting in online casino or bingo [ 14 , 15 , 16 , 17 ], the latter being the gambling types less affected by COVID-19. Thus, it is possible that COVID-19-related effects on the gambling market may affect women and men differentially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that money that should be used for other purposes is spent on gambling is a potential source of guilt. Studies found that women that gamble are more prone to experience feelings of guilt and shame [ 42 , 43 ]. Again, this has consequences for prevention and feedback to gamblers.…”
Section: Discussionmentioning
confidence: 99%